Geo-Information Modeling for Determining the Movement of Human Capital - R. V. Fattakhov; P. V. Stroev; M. M. Nizamutdinov; O. V. Pivovarova; M. I. Akhmetzyanova (Управленческие науки)
The paper considers the application of Geographic Information Systems (GIS) to assess the attractiveness of territorial entities of the Russian Federation in terms of the movement of human capital. The relevance of the study is because of the uneven distribution of human capital, the high rate of its migration from underdeveloped regions and municipalities, and the insufficient effectiveness of the policy pursued by regional authorities and local self-government. The purpose of the research is to develop a GIS monitoring of the socio-economic attractiveness of municipalities to determine the movement of human capital. The research methodology is based on the use of complex and statistical analyses, methods of geo-information modeling. The information basis of the study is the data of the regulatory legal framework of reference systems, official statistics of the Republic of Bashkortostan, and investment passports of municipal districts and cities of the region. The authors justify and formulate a list of requirements and limitations for the GIS software and tool complex. Also, the authors identified and disclosed the requirements for GIS information support: reliability, completeness, relevance, consistency, understandability (unambiguity). There have been generated major conditions for the correct operation of the GIS software for monitoring the attractiveness of municipalities, considering the limitations of the current legislation. The research developed and described the functional basis of the GIS, which includes two key components with corresponding structural elements and tools: an organizational block and a modeling and visualization block. The authors proposed a list of key statistical (attribute) and spatial data and the attractiveness coefficient of a municipality as a criterion for assessing the opportunities for the development of human capital in a particular territory. The authors developed the scheme of the algorithm for the functioning of GIS monitoring the attractiveness of municipalities of the Republic of Bashkortostan, as well as they introduced the interface and user tools. The proposed GIS allows users to search for the municipality with the subsequent output of information about it containing the values of demographic, migration, socio-economic and environmental indicators in tabular and graphical forms. The results of the research make it possible to predict the level of attractiveness of municipalities in the short and medium term, depending on the chosen governance strategy and also allow zoning of municipalities by groups. The authors conclude they developed GIS monitoring of socio-economic attractiveness of municipalities to determine the movement of human capital in the Republic of Bashkortostan can serve as the basis for creating a fully functional decision support system at the regional level in all subjects of the Russian Federation.